Liquid‐Crystal‐Mediated Self‐Assembly of Porous α‐Fe2O3 Nanorods on PEDOT:PSS‐Functionalized Graphene as a Flexible Ternary Architecture for Capacitive Energy Storage. (30th November 2015) - Islam, Md. Monirul; Cardillo, Dean; Akhter, Taslima; Aboutalebi, Seyed Hamed; Liu, Hua Kun; Konstantinov, Konstantin; Dou, Shi Xue
Abstract : A novel aqueous‐based self‐assembly approach to a composite of iron oxide nanorods on conductive‐polymer (CP)‐functionalized, ultralarge graphene oxide (GO) liquid crystals (LCs) is demonstrated here for the fabrication of a flexible hybrid material for charge capacitive application. Uniform decoration of α‐Fe2 O3 nanorods on a poly(3, 4‐ethylene‐dioxythiophene): poly(styrenesulfonate) (PEDOT:PSS)‐functionalized, ultralarge GO scaffold results in a 3D interconnected layer‐by‐layer (LBL) architecture. This advanced interpenetrating network of ternary components is lightweight, foldable, and possesses highly conductive pathways for facile ion transportation and charge storage, making it promising for high‐performance energy‐storage applications. Having such structural merits and good synergistic effects, the flexible architecture exhibits a high specific discharge capacitance of 875 F g −1 and excellent volumetric specific capacitance of 868 F cm −3 at 5 mV s −1, as well as a promising energy density of 118 W h kg −1 (at 0.5 A g −1 ) and promising cyclability, with capacity retention of 100% after 5000 charge–discharge (CD) cycles. This synthesis method provides a simple, yet efficient approach for the solution‐processed LBL insertion of the hematite nanorods (HNR) into CP‐functionalized novel composite structure. It provides great promise for the fabrication of a variety of metal‐oxide (MO)‐nanomaterial‐based binder and current collector‐free flexible composite electrodes for high‐performance energy‐storage applications. Abstract : A liquid‐crystalline novel self‐assembly approach is used to develop a flexible material for charge capacitive applications. Highly porous hematite (α‐Fe2 O3 ) nanorods (HNRs) prepared by an advanced spray‐precipitation method enable the fabrication with ultralarge graphene oxide (GO) functionalized by PEDOT:PSS in an aqueous medium to develop a novel self‐assembled 3D architecture with excellent energy‐storage performance.